The concept of the average stress in the fracture process zone for the search of the crack path - Yu.G. Matvienko; M.M. Semenova (Fracture and Structural Integrity)
The concept of the average stress has been employed to propose the maximum average tangential stress (MATS) criterion for predicting the direction of fracture angle. This criterion states that a crack grows when the maximum average tangential stress in the fracture process zone ahead of the crack tip reaches its critical value and the crack growth direction coincides with the direction of the maximum average tangential stress along a constant radius around the crack tip. The tangential stress is described by the singular and nonsingular (T-stress) terms in the Williams series solution. To demonstrate the validity of the proposed MATS criterion, this criterion is directly applied to experiments reported in the literature for the mixed mode I/II crack growth behavior of Guiting limestone. The predicted directions of fracture angle are consistent with the experimental data. The concept of the average stress has been also employed to predict the surface crack path under rolling-sliding contact loading. The proposed model considers the size and orientation of the initial crack, normal and tangential loading due to rolling–sliding contact as well as the influence of fluid trapped inside the crack by a hydraulic pressure mechanism. The MATS criterion is directly applied to equivalent contact model for surface crack growth on a gear tooth flank.